Religious Changes in Montenegro: From the Socialist Atheization to Post-Socialist Revitalization - Bakrač, Vladimir (Occasional papers on religion in Eastern Europe, 2020)
The influence, significance, and meaning of religion and religiosity in the Balkans at the end of the second decade of the 21st century have not diminished. Peter Berger argues that today’s world, with some exceptions, is deeply religious—perhaps even more than before. This attitude of Berger refers to modern society, but in the era of socialism, it was not so. Empirical verification from that period records the atheization and secularization of society. In this regard, the primary aim of this paper is to present a kind of panoramic review of religiosity from the era of socialism to the post-socialist transformation and religious revitalization. The focus of the first part of the paper is the analysis of de-monopolization and stigmatization of religion in socialism while the second part of the paper concerns the analysis of the elements of desecularization of society, and the post-socialist revitalization of religion in Montenegro. Subsequently, a kind of stability in religiosity is detected on the basis of empirical material.